The Influence Of Organizational Support And Motivation On Organizational Commitment Of Employees At Pt Mitra Aneka Rezeki (MAR) Natai Raja In Kubu Raya Regency - Umi Khoyriah; Arninda Arninda (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to examine the influence of Organizational Support and Motivation on Organizational Commitment among employees at PT Mitra Aneka Rezeki (MAR) Natai Raja in Kubu Raya Regency. A quantitative approach using multiple linear regression analysis was employed to analyze the relationships between the variables. The sample consisted of employees with varying demographic characteristics, such as age, gender, education, work experience, and income. The findings reveal that both Organizational Support and Motivation have a significant positive impact on Organizational Commitment. The multiple linear regression equation derived from the analysis is Y = 0.519 + 0.816 X1 + 0.082 X2, where X1 represents Organizational Support and X2 represents Motivation. The correlation coefficient (R = 0.776) indicates a strong relationship between the independent variables and Organizational Commitment, while the coefficient of determination (R² = 0.602) suggests that 60.2% of the variation in Organizational Commitment can be explained by Organizational Support and Motivation. The results of the F-test (0.000) indicate that the independent variables together have a significant effect on Organizational Commitment, and the T-test shows that both variables individually influence Organizational Commitment. This study highlights the importance of fostering a supportive work environment and motivating employees to enhance their commitment to the organization. However, limitations such as the sample size and the focus on only two variables suggest that further research should explore additional factors and include a broader sample for more generalizable results.